A Study to Assess the Implementation and Effectiveness of IMNCI Program and Evaluation of Skills of Rural Anganwadi Workers in Vadodara Taluka - Sheela Bharani; Tarun Parmar; Neha Kantharia; Rahul Parmar; Nikhil Kharod (Medsci Publications, 2012)
Background: IMNCI is an integrated approach to decrease morbidity and mortality amongst children between 0-5 years. Training to pre-service level during medical, nursing-education and anganwadi worker (AWW) is the first fundamental stage of IMNCI. Objectives: To evaluate the skills of AWWs trained under the IMNCI program and to identify the problems in implementation of IMNCI program in rural areas. Methods: A cross sectional study including 50 AWWs of Vadodara taluka, selected by random sampling technique. Results: Most of the AWWs were ≤40 years of age. Out of 50 AWWs, 18 (36%) underwent IMNCI training between 1-2 years duration and 32 (64%) underwent training between 2-5 years period from the date of interview. Around 72% AWWs undertook 3 visits of young infants. All AWWs were equipped with weighing scales but were not having supplies like, ORS (70%), Cotrimoxazole (94%) and IFA (56%). Out of 46 (96%) who had maintained the register, only 9 (18%) had completed them. Lack of motivation and supervision with overburden due to other programs and inadequate stocks of drugs were major difficulties found in this program. Convulsions, lack of active body movements and nasal flare in young infants were the signs missed by 36%, 22% and 20% AWWs respectively. About 50% AWWs had knowledge about Kangaroo mother care. Breast-feeding problems were identified by 54% AWWs. Only 8% AWWs had checked immunization cards. Conclusion: The study identified a number of programme-related and external constraints that, if taken care of, might improve implementation and effectiveness of IMNCI program.